Population size and the size of government - Tim Krieger; Daniel Meierrieks (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine the effect of population size on government size for a panel of 130 countries for the period between 1970 and 2014. We show that previous analyses of the nexus between population size and government size are incorrectly specified and fail to consider the influence of cross-sectional dependence, non-stationarity and cointegration. Using a panel time-series approach that adequately accounts for these issues, we find that population size has a positive long-run effect on government size. This finding suggests that effects of population size that increase government size (primarily due to the costs of heterogeneity, congestion, crime and conflict) dominate effects that reduce government size (primarily due to scale economies).
Keywords: H11; H50; 330; government size; population size; non-stationary; cross-sectional dependence; panel cointegration